Morpho-phylogenetic insights reveal Bisporella montana as Calycina montana comb. nov. (Pezizellaceae, Helotiales) - Lestari, Anis S.; Chethana, K. W. Thilini (Phytotaxa, 2022)
Calycina-like specimens were collected in Doi Inthanon National Park, Thailand. The combined phylogeny of ITS and LSU based on maximum likelihood and bayesian inference analyses confirmed the taxonomic placement of our specimen in Pezizellaceae. Based on morphology and multi-gene phylogeny, the new discomycete specimen was identified as Calycina montana comb. nov., and was documented for the first time in Thailand. Calycina montana is characterized by the amber color, stipitate apothecia, gelatinized ectal excipulum, cylindrical asci and ellipsoidal ascospores. The morphology was observed together with the type strain, Bisporella montana. Our phylogenetic analyses and observation of the morphology of the type strain also confirmed the new combination of Bisporella shangrilana as Calycina shangrilana comb. nov., which resolves the confusion of Bisporella placement in Pezizellaceae.